Effectiveness of Chemical Castration Sanctions and the Principle of Non-Discrimination: A Human Rights, Islamic Law, and SDGs Perspective - Muhamad Adystia Sunggara; Selcuk Koca (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the application of chemical castration sanctions and the principle of non-discrimination from the perspective of criminal law and human rights in Indonesia, as well as to review these policies from the perspective of Islamic law (maqasid al-shariah) and the Sustainable Development Goals (SDGs). Theoretical framework: The theoretical framework of this research uses the concept of the rule of law, the principles of criminal law and human rights, the concept of maqasid al-shariah in Islamic law, and the perspective of SDGs related to justice, health, and the reduction of inequality. Literature review: A literature review analyzes various laws and regulations, court decisions, and academic studies related to the application of chemical castration sanctions as a legal phenomenon. Methods: The research uses normative juridical methods with a literature study approach through the analysis of laws and regulations, court decisions, legal journals, and law enforcement reports. Results: The results of the study show that the effectiveness of chemical castration sanctions is still in doubt and has the potential to contradict the principle of non-discrimination in the 1945 Constitution, ICCPR, and other international human rights instruments. Implications: Chemical castration policies create a dilemma between the protection of communities from sexual crimes and the protection of the human rights of perpetrators, as well as the debate from an Islamic perspective of Islam and the SDGs related to health, justice, and welfare. Novelty: The novelty of this research lies in the integrative analysis of chemical castration sanctions from the perspective of criminal law, human rights, Islamic law (maqasid al-shariah), and SDGs.